2006
DOI: 10.1152/ajpcell.00451.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8: novel roles in human airway smooth muscle cell contraction and migration

Abstract: In patients with cystic fibrosis (CF) and asthma, elevated levels of interleukin-8 (IL-8) are found in the airways. IL-8 is a CXC chemokine that is a chemoattractant for neutrophils through CXCR1 and CXCR2 G protein-coupled receptors. We hypothesized that IL-8 acts directly on airway smooth muscle cells (ASMC) in a way that may contribute to the enhanced airway responsiveness and airway remodeling observed in CF and asthma. The aim of this study was to determine whether human ASMC (HASMC) express functional IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 56 publications
8
89
1
3
Order By: Relevance
“…We confirmed that CCL5 was a major contributor to the chemotactic activity of HRV-CM for ASMC by demonstrating that incubation of HRV-CM with a specific blocking antibody to CCL5 largely abolished ASMC chemotaxis. Taken together our data are consistent with earlier reports that CCL5 derived from TNFα-stimulated epithelial cells was chemotactic for ASMC (30), and that CXCL8 can also stimulate ASMC migration (25,30).…”
Section: Hrv-induced Asmc Migration Is Mediated At Least In Part VIsupporting
confidence: 93%
“…We confirmed that CCL5 was a major contributor to the chemotactic activity of HRV-CM for ASMC by demonstrating that incubation of HRV-CM with a specific blocking antibody to CCL5 largely abolished ASMC chemotaxis. Taken together our data are consistent with earlier reports that CCL5 derived from TNFα-stimulated epithelial cells was chemotactic for ASMC (30), and that CXCL8 can also stimulate ASMC migration (25,30).…”
Section: Hrv-induced Asmc Migration Is Mediated At Least In Part VIsupporting
confidence: 93%
“…TGF-b1 mediates many of its actions by stimulating the release of additional growth factors and inflammatory mediators from airway structural cells. In HASM cells, TGF-b1 stimulates the expression of COX-2 and the release of PGE-2 and IL-8 (118), mediators demonstrated to affect HASM contractile or fibrotic responses (119)(120)(121). In addition, TGF-b1-induced mediator release from the airway epithelium may affect contractile or fibrotic function in HASM cells.…”
Section: Contraction Cell Shortening and Cytoskeletal Motorsmentioning
confidence: 99%
“…Human ASMCs were isolated from lung transplant donors and prepared as described previously (32). The protocol was approved by institutional research ethics boards of the McGill University Health Centre and the Université de Montréal, Montreal, QC, Canada and informed consent for ASMC harvesting was obtained at surgery or at the time of lung transplantation.…”
Section: Culture Of Human Asmcsmentioning
confidence: 99%